HOTSPOTS AND MANTLE PLUMES: GLOBAL INTRAPLATE TECTONICS, MAGMATISM AND ORE DEPOSITS - Pirajno F. (My University, 2004)
Intraplate tectono-magmatic phenomena, including the emplacement of layered intrusions, and the giant dyke swarms, anorogenic (hotspot) volcanism, oceanic plataeux, rifting processes, basin formation, and geomorphological features are discussed in the context of the mantle plume theory. A review of the relationships between mantle plumes and ore deposits focuses on direct links, proxied by the emplacement of mafic-ultramafic magmas (e.g. PGE and Ni–Cu sulphides associated with flood basalts) and indirectly in rift systems where high geothermal gradients are set up in the crust above the plume, induce large scale circulation of hydrothermal fluids, which result in the generation of a wide range of ore deposits. Peak periods in the deposition of iron formations coincide with plume events in the Archeaen and Proterozoic. Passive margins, which evolve from continental breakups and triple junctions, host abundant mineral and hydrocarbon resources.